Método combinatorio en el estudio de sistemas finitos y su aplicación en la solución de problemas de programación matemática - Calderón Beltrán, Elmer Rusbert (2019)
The combinatorial optimization problems have a simple formulation and since_x000D_ the set of possible solutions is nite, it can be thought of being an easy problem to_x000D_ address, however, the number of possible solutions can be so great that obtaining_x000D_ the solution at any given time, with existing methods and technical means, can be_x000D_ an impossible task._x000D_ In this paper we present the combinatorial-approximate method proposed by V._x000D_ Khachaturov to address these problems. This method is based on the construction of_x000D_ approximate functions and then from certain optimization criteria we can determine_x000D_ the optimal solution of the problem or a subset where it is located. We will present_x000D_ the construction of some classes of approximate functions, and we will use it in_x000D_ the combinatorial-approximate method to solve the entire programming problem_x000D_ with two or more restrictions. We also present the implementation in C++ for an_x000D_ approximate function